Effect of Game-based Learning using Live Streaming on Learners' Interest, Immersion, Satisfaction, and Instructors' Perception - Woo-Hyun Lee; Han-Moi Shim; Hyung-Gi Kim (Serious Games Society, 2022)
The method of using games in class has been recognized for its effectiveness through the efforts of many researchers, and has spread mainly in the United States and Europe, and the number of cases implemented in actual education has increased. Nevertheless, many people have preconceived notions about games and distrust the effects of game-based learning and show negative attitudes. In fact, there are limitations and disadvantages of game-based learning, and it is difficult to overcome them. More than half of the inconveniences or problems of teachers who want to try game-based learning revealed by the 2009 survey have not been solved yet. Due to the sudden spread of COVID-19, the Ministry of Education has issued a policy to convert classes at schools and academies into non-face-to-face. The full-scale non-face-to-face class, which was conducted based on the high penetration rate of smartphones and Internet penetration in Korea, allows all students to take non-face-to-face learning using the Internet, It can be interpreted that even if there are students who cannot take classes, the right to equality is recognized because there are very few. Non-face-to-face classes have the characteristics that instructors and learners will be spatially separated, spatially simultaneous, interactive, and teaching and learning behavior will be mediated by the screen. And these features are common to live streaming. Taking advantage of this, this study aims to approach improving the perception of game-based learning as an advantage of "watching games" beyond "playing games" by using live streaming for game-based learning. This study conducted game-based learning and game streaming learning for 210 third-year middle school students, compared the effects of game-based learning on learning interest, immersion, and satisfaction with the results of previous studies to verify the design and prove the combined effect of live streaming and game-based learning. In addition, in-depth interviews with instructors who conducted game-based learning confirmed that awareness of the introduction, value, and finance of game-based learning improved.